The Columbia companion to American history on film how the movies have portrayed the American past - Rollins, Peter C. (Gale virtual reference library, 2003)
Collection of essays that explore how major eras, institutions, peoples, wars, leaders, social groups, and myths of our national culture have been portrayed on film.